Optimalisasi Kepemimpinan Kewirausahaan: Studi Kasus Pada Sekolah Menengah Kejuruan - Agustin Hanivia Cindy; Sugiyono Sugiyono; Husaini Usman (Lentera: Jurnal Ilmiah Kependidikan, 2022)
The importance of optimizing leadership in educational institutions has now become an absolute necessity to achieve maximum results. This study highlights the implementation of leadership as a means to leverage various resources, explore opportunities, solve challenges and lead organizations to successfully achieve goals. In particular, this case study research has the aim of reviewing and implementing the implementation of innovation and entrepreneurial leadership of school principals in creating a learning environment. Thirty vocational high school teachers and two vocational high school principals acted as informants in this study. Through the use of Miles and Huberman's interactive qualitative analysis model, the results of his research indicate that the principal in implementing entrepreneurial leadership uses two ways. First, the principal manages organizational growth by optimizing, communicating, motivating, monitoring, controlling, exemplary and empowering. Second, the principal creates innovation through several improvements: vision building, staff development and restructuring. The implication is that it can create a positive learning environment for school members, encouraging them to innovate in academic and non-academic fields. It is necessary to help principals create a positive learning environment. In addition, the findings of this study can be a reference for applying entrepreneurial leadership to support teachers and students in making some innovations.